Influence of external perturbations on the interaction between grains in plasma - E A Lisin; R A Timirkhanov; O S Vaulina; O F Petrov; V E Fortov (New Journal of Physics, 2013)
An experimental study of dust grain dynamics in plasma was carried out for cluster systems relaxing to their equilibrium state after the action of a laser beam. The influence of this external perturbation on the potential between interacting dust grains was analyzed. We found that the spatial asymptotes of the pair potential for perturbed and equilibrium dust systems differ. The possible reasons for this phenomenon are discussed.